Pelatihan Pembuatan Soal Numerasi Berbasis Asesmen Kompetensi Minimum (AKM) Bagi Guru SD Di Kota Ternate - Ahmad Afandi; In Hi Abdullah; Marwia Tamrin Bakar; Ariyanti Jalal; Ardiana Ardiana (UKInstitute, 2023)
Minimum Competency Assessment (AKM) is an activity that is routinely carried out every year. The question used in AKM activities is the Numeracy Problem. However, the ability and skills of elementary school teachers in Ternate city in making numeracy questions are still low. The purpose of the service activity is to improve the ability and skills of teachers in Ternate city in making AKM-based numeracy questions. The partners of this activity are UPTD Ternate Selatan, UPTD Ternate Tengah, and UPTD Ternate Utara. The number of participants in this activity is 50 teachers. The method carried out lectures, discussions, assignments, and questions and answers with data retrieval techniques using questionnaires. The result of the service activity is an increase in the ability and skills of teachers in Ternate city in making AKM-based numeracy questions. Making AKM-based numeracy questions is effectively carried out by training methods.